PEREMPUAN DALAM BINGKAI MEDIA MASSA - Agus Setiaman (Jurnal Kajian Budaya dan Humaniora, 2025)
Abstract Discussion of mass media cannot be separated from the interests behind the media, especially the interests in the information it conveys. In the development of modern mass media, there are at least two main interests behind the media, namely economic interests and power interests that shape media content, the information presented and the meaning it offers. Between these two main interests, there is actually a more basic interest that is often ignored, namely the public interest. The media, which should act as a public sphere due to the interests above, actually ignores the public interest itself. The strength of economic interests and political interests is what actually makes the media unable to be neutral, honest, fair, objective, and open. As a result, the information presented by the media has raised serious problems of objectivity of knowledge in the media itself. Keywords: Mass Media, Public, Interests, Economy, Politics